The effect of distracters on student performance on the force concept inventory - Rebello, N. Sanjay; Zollman, Dean A. (American Association of Physics Teachers, 2013)
We have compared students’ responses on four multiple-choice force concept inventory ~FCI! questions with similar responses to equivalent open-ended questions. Our results indicate a good agreement between the percentages of correct responses in each of the two formats, indicating that distracters on the FCI do not adversely affect performance as measured by the number of correct answers. However, a significant percentage of the open-ended responses fall into categories that are not included in the FCI multiple choices. When these alternative categories were presented to the students as distracters in a revised multiple-choice format, a significant percentage of the students chose these alternative responses
Keywords: Force concept inventory; Distracters; Student performance; Physics